Self‐Powered Ultraviolet Photodetectors Driven by Built‐In Electric Field - Su, Longxing; Yang, Wei; Cai, Jian; Chen, Hongyu; Fang, Xiaosheng (Small (Weinheim an der Bergstrasse, Germany), 2017)
Self‐powered ultraviolet (UV) photodetectors, which have vast applications in the military and for civilian purposes, have become particularly attractive in recent years due to their advantages of high sensitivity, ultrasmall size, and low power consumption. In particular, self‐powered UV photodetectors driven by a built‐in electric field cannot only detect UV signals but also be powered by the incident signals instead of external power. In this concept, the key issues and most recent developments on photovoltaic type UV photodetectors driven by p–n homojunction, heterojunction, and Schottky junction are surveyed. This should generate extensive interest in this field and encourage more researchers to engage in and tackle the scientific challenges. In this Concept, self‐powered UV photodetectors driven by a built‐in electric field are presented, which is extremely important for applications in UV detection. The key issues and developments of photovoltaic‐type UV photodetectors driven by the p–n homojunction, heterojunction, and Schottky junction are surveyed. Additionally, the development tendency of next generation photovoltaic‐type UV is also proposed.